Using a 360° Camera to Record Natural Dyeing Craft Practice - Pagett, Beth (FormAkademisk, 2023)
In recent years, 360° video cameras have become increasingly accessible and are now being used as valuable research tools across a range of disciplines. Their wide and flexible field of vision can provide immersive and/or alternative perspectives compared to standard video. This paper will present emerging findings from using a 360° video camera to capture natural dye craft practice from an auto-ethnographic perspective and as an observer of other dyers’ practice during fieldwork visits. The 360° video data forms part of my doctoral study, in which I explore the embodied interactions between people, plants and materials that connect practitioners to their surroundings, linking them to other species and ecologies. The varied nature of the actions and processes that form the craft practice (e.g. foraging, tending, harvesting, mordanting, dyeing), and the different places and spaces in which these actions occur, presented a practical and observational challenge when trying to record the practice in a video format. Using a 360° camera proved to be a flexible, data-rich and engaging method for recording the craft. The ability to ‘move’ around and explore different perspectives from within the video after it was recorded was especially valuable, allowing a shift in the focus of the recording and presenting the opportunity to actively centre or decentre plants, people and materials. In this paper, I will reflect on my experiences recording and working with 360° video data and discuss some of the limitations and possible benefits of using this equipment in a craft research setting.